Comparative efficacy of statins, metformin, spironolactone and combined oral contraceptives in reducing testosterone levels in women with polycystic ovary syndrome: a network meta-analysis of randomized clinical trials - Hussain H. Almalki; Turki M. Alshibani; Abdullah A. Alhifany; Omar A. Almohammed (BMC, 2020)
Abstract Background Polycystic ovary syndrome (PCOS) is an endocrine disorder affecting about 10% of women in reproductive age and associated with a variety of hormonal abnormalities, including hyperandrogenemia and infertility, all of which could lead to PCOS. Statins were previously introduced as a therapeutic option for reducing testosterone levels in women with PCOS, either alone or in combination. The aim of this study is to evaluate the effectiveness of different statins alone or in combination with metformin in reducing testosterone levels in women with PCOS. Methods Medline, Embase, and clinicaltrials.gov were searched for studies that investigated the efficacy of statins, metformin, spironolactone, or combined oral contraceptives (COCs), individually or in combination, in reducing the testosterone level in patients with PCOS. The search was limited to randomized clinical trials and conducted according to the preferred reporting items for systematic reviews and meta-analyses - extension statement for network meta-analyses (PRISMA-NMA). The quality of included studies was assessed using the Cochrane Collaboration risk of bias (RoB) assessment tool. A frequentist network meta-analysis using random-effects models was used to assess the efficacy in reducing testosterone level and were expressed as odds ratios (OR) and 95% credible interval (95%Crl). All statistical analyses were performed using netmeta Version 1.0 on R statistical package. Result Nine RCTs involving 613 patients were included. Atorvastatin showed greater reduction in testosterone level compared to COC (MD −2.78, 95%CrI −3.60, −1.97), spironolactone plus metformin (MD −2.83, 95%CrI −3.80, −1.87), simvastatin (MD −2.88, 95%CrI −3.85, −1.92), spironolactone (MD −2.90, 95%CI −3.77, −2.02), simvastatin plus metformin (MD −2.93, 95%CrI −3.79, −2.06), metformin (MD −2.97, 95%CrI −3.69, −2.25), lifestyle modification (MD −3.02, 95%CrI −3.87, −2.18), and placebo (MD −3.04, 95%CrI −3.56, −2.53). Conclusion Atorvastatin was found to be more effective than the other management strategies in reducing the total testosterone level for patients with PCOS. Future studies should focus on the optimal dose.